Desarrollo y evaluación de un fotobiorreactor para fijación de co2 obtenido como subproducto de la combustión de fuentes fijas (2022)
The rising greenhouse gas emission in the atmosphere is a serious environmental problem. Particularly, the rising carbon dioxide (CO2) emissions heavily affect our planet and contribute to global warming. For this reason, the scientists face the challenge to develop alternative methods to decrease the emitting sources and the carbon dioxide emissions. One option is CO2 sequestration by microalgae. Thus, the biological carbon dioxide sequestration is recommended as an environmentally friendly approach to capturing and converting CO2 into products with added value, through refineries based on the harvesting of PMs (photosynthetic microorganisms).